Forma wykluczenia "bonum prolis" w doktrynie i orzecznictwie Roty Rzymskiej - Gołębiowska, Anna (Ius Matrimoniale, 2012)
Issues concerning the procreation and upbringing of children has always been of special concern of the Church and appeared in the regulation of rights on the basis of Marriage Canon Law. Codex of John Paul II in 1983, contains no provisions that define marriage invalid because of the exclusion of offspring. The decision of the Roman Rota that it evokes the title of the exclusion of offspring, as a second source of nullity of marriage. The Roman Rota judges stress that the positive act of will contrary to the essential purpose of marriage, which is the procreation and education of offspring has the same effect as a condition contrary to the essence of marriage. At the focus issues of jurisprudence in the form of exclusion of children received the case law of the Roman Rota, which have the competence of the interpretation of the law. The Roman Rota judges indicate that the selected candidates must demonstrate evidence that the person containing marriage ruled out having children forever, or postponed the decision to have children at some time, but with the indication of the circumstances, the reasons for its decision. Decisions given by the Roman Rota Tribunals show all the particular Churches of significant occupational exposure limits and terms. In addition, a major source of knowledge of canon law. Thus, marriage invalidly contains one who in a certain way limits the marital consensus or a positive act of will exclude the offspring by avoiding the conception or by abortion or kill the unborn child.